Results 1 to 2 of 2
  1. #1
    Join Date
    Oct 2007

    Problem with converting 2nf to 3nf.

    Im learning on my own on normal forms, and i am stuck on how to perform this.

    Relation R(K, P, R, S) is in 2NF.
    Given the following (transitive) dependency:
    P, Q -> R
    Convert R into two-or-three relations, R1, R2, R3 all in 3NF..

    i can only understand how to do the first relation, but how would you do the other.

    R1(PQ -> R)

    thanks for any help.

  2. #2
    Join Date
    May 2005
    San Antonio, Texas
    Oh wow.. I will try to reply with something but its been a few years since ive even looked at functional dependencies and when I did I had no idea what I was doing :P

    if P, R, S -> K and P, Q -> R then P, Q, S -> K (transitivity I think :P hehe)
    P, Q is a subset of R so R, Q, S -> K (I might have use that wrong)

    R1(K, R, S)
    R2(R, P, Q)

    Forgive me if I butchered this.. I tried hehe.

Posting Permissions

  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts